State Fiscal Reforms in India : Progress and Prospects - World Bank (Washington, DC, 2013)
Following two decades of relatively rapid growth, and a decade of liberalization, there is growing confidence within India, as well as internationally, about the state of the economy, and India's development potential. Nonetheless, and particularly since the late nineties, when India's states experienced a sharp fiscal deterioration, they have faced a squeeze on development spending, particularly acute in the poorer ones. In response, most state governments embarked on fiscal reforms, aimed at reducing deficits, and enabling effective interventions in priority areas. States in India play an increasingly important role in devising, and implementing policies to stimulate economic growth, and promote human development. But the performance of India's states is increasingly divergent, State deficits and debt levels rose sharply in the late nineties, and off-budget liabilities also increased rapidly. This sharp fiscal deterioration gave rise to state-level fiscal adjustment efforts, which in recent years have shown some signs of improved fiscal performance. Concerns about the level, and composition of fiscal deficits remain. The report states that a halt in reforms would endanger the states quality and quantity of productive expenditures, while debt levels would steadily build. It reviews expenditure reforms - particularly salaries, at the core of expenditure restructuring - and, pensions as a rapidly-mounting liability, which can be contained by parametric reforms, and longer-term structural reforms, while also examines subsidies, exemplifying the difficulties involved in reforming subsidy regimes. Regarding power sector reforms, commercial discipline should be a top priority. Public enterprise reforms are outlined, suggesting that while immediate fiscal gains may not be achieved, such reforms will prevent future budgetary support from keeping loss-making enterprises afloat. On examining revenue reforms, the report indicates these are essential to reduce fiscal imbalances, suggesting the elimination of tax on inter-state exports is critical, and should proceed with, or without the value-added tax (VAT), specifying tax administration reforms are perhaps more important than tax reforms. On strengthening the fiscal federal framework, it is recommended States need more flexibility to borrow, but under a centrally-imposed aggregate borrowing cap. Three institutional reform would therefore help fiscal federalism in India: Finance Commission as a permanent body; entrusting a single agency in compiling timely state-level fiscal data; and, reviewing the role of the Planning Commission.